Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Join our platform to connect with experts ready to provide precise answers to your questions in various areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

f(x) = 5 + 4x2, then f(3) =

Sagot :

Step-by-step explanation:

To answer this, we need to plug in 3 as x in the equation f(x) = 5 + 4x².

That would look like this: f(3) = 5 + 4(3)²

f(3) = 5 + 4(3)²

f(3) = 5 + 36

f(5)=41

Therefore, the answer is 41.

I hope this helps!! :)